Aseptic Meningitis in Pregnancy – A Case Study Detailing Potential Diagnostic Dilemmas - NG, Yan Shun; Sze Minn GOH, Marlene Samantha; Mathur, Manisha (Clinical Journal of Obstetrics and Gynecology, 2023)
There are few reported cases of meningitis in pregnancy and presentation can be variable in each patient which may cause diagnostic challenges and potential delays in treatment. Here, we discuss a case of aseptic meningitis - a 36 years old Gravida 2 Para 1 pediatric physician with “the worst headache of her life” at 31+5 weeks of gestation. At presentation, she did not have any of the classic triads of meningitis (fever, neck stiffness, and/or a change in mental status) and did not report any neurological symptoms. In view of persistent headache, development of pyrexia, and evolving symptoms of photophobia, she was referred to a neurology specialist, and a lumbar puncture was performed. Findings were in line with meningitis and the polymerase chain reaction confirmed enterovirus meningitis. Although aseptic meningitis is rare, it should be considered as a differential diagnosis in patients with persistent complaints, development of associated symptoms of pyrexia, photophobia, and neck pain, as well as in patients with increased risk of exposure to viral illnesses.